PEMBERDAYAAN MASYARAKAT DALAM MEMANFAATKAN LAHAN TIDUR DI PEKARANGAN RUMAH GUNA MENINGKATKAN PENDAPATAN RUMAH TANGGA DI DESA IWOI MOPURO KECAMATAN WOLO KABUPATEN KOLAKA - Rostin, Rostin; Millia, Heppi; Balaka, Yani; Gamsir, Gamsir; Suriadi, La Ode; Rumbia, Wali Aya; Rahim, Manat; Nuddin, Nuddin (Jurnal Pengabdian Masyarakat Sabangka, 2025)
The purpose of this service is to educate and motivate the community in Iwoi Mopuro village in empowering idle land around the yard. So that it is planted with food and medicine that can increase family income and spending efficiency. In order to anticipate changes in social, economic and environmental order that can occur due to environmental changes that cause food and medicine prices to increase. So that it needs to be worked around by rural communities who are very limited. The results of this service have increased the understanding of service participants in utilizing idle land in the yard to increase income and make family spending more efficient. The participants who are driven by the village head as the PKK Activist will create a pilot area for medicines in the yard of one of the participants, so that it can be followed by residents.